Strengthening the Health System to Better Confront Noncommunicable Diseases in India - Duran, Antonio (Medknow Publications & Media Pvt Ltd, 2011)
The paper emphasizes the vital need to address the rising burden of noncommunicable diseases (NCDs) in India with a health systems approach. The authors argue that adoption of such approach may soon be imperative. Applying the health systems framework developed by the WHO in 2000 to NCDs means in summary re-examining the planning and organization of the entire health system, from service provision to financing, from information generation to ensuring adequate supply of pharmaceuticals/technologies or human resources, from improving facility management to performance monitoring. Using this framework the authors seek to highlight core issues and identify possible policy actions required. The challenge is to ensure the best implementation of what works, aligning the service provision function with the financial incentives, ensuring leadership/stewardship by the government across local/municipal, state or regional and national level while involving stakeholders. A health system perspective would also ensure that action against NCD goes hand in hand with tackling the remaining burden from communicable diseases, maternal, child health and nutrition issues.